Risk Factors for Suicide Attempt in Drug Abusers - farideh faraji; Neda Kakayi; Mohammad Kazem Atef Vahid; Ahmad Sohraby; Samira Purghorbani (Drug Control Headquarters, Research and Education Office, 2015)
Objective: The present study was conducted to identify risk and prediction factors of suicide attempts among drug abusers. Method: This causal-comparative study was conducted on 91 drug abusers that included 42 male and female suicide attempters and 49 male and female counterparts. Millon multi-axial personality inventory-II (MCMI-II), Dass-42 (depression, anxiety, stress), and coping styles inventory were used for data collection purposes. Results: The highest rate of suicide attempt was found in young male drug abusers with these characteristics: single, junior school graduate, unemployed, suicide history, sex and physical abuse history during childhood, legal problems, suicide and self-injury witness, and violence and suicide in family members. Compared to non-attempters, suicide attempters obtained higher scores in depressive, obsessive, masochistic, and borderline personality disorders clinical somatoform symptoms, alcohol abuse in addition to drug use, major depressive disorder, and stress. Suicide attempters also used lower levels of task-focused and avoidance-focused strategies and higher levels of emotion-focused strategies to cope with stressors. Conclusion: The findings of this study can contribute to suicide identification and prevention among drug abusers.